Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1177/00220345211049403
|View full text |Cite
|
Sign up to set email alerts
|

Gas1 Regulates Patterning of the Murine and Human Dentitions through Sonic Hedgehog

Abstract: The mammalian dentition is a serially homogeneous structure that exhibits wide numerical and morphological variation among multiple different species. Patterning of the dentition is achieved through complex reiterative molecular signaling interactions that occur throughout the process of odontogenesis. The secreted signaling molecule Sonic hedgehog (Shh) plays a key role in this process, and the Shh coreceptor growth arrest-specific 1 (Gas1) is expressed in odontogenic mesenchyme and epithelium during multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Differentially expressed circRNAs were found in elderly patients with OP, and through further experiments, it was found that circRNA008876 can play a biological role as an miR-150-5p sponge ( 49 ), which provides a potential biomarker and therapeutic target for senile OP. A previous study showed that Shh coreceptor growth arrest-specific 1 (GAS1) is expressed in mesenchymal cells, and in a GAS1-deficient mouse model, mice have abnormal dentition ( 50 ). Another study has also shown that inhibiting the expression of circ_0003865 in patients with OP can promote the osteogenic differentiation of BMSCs, and that circ_0003865 regulates the expression of the GAS1 gene by sponging miR-3653-3p ( 51 ).…”
Section: Associations Between Circrnas and Bmscsmentioning
confidence: 99%
“…Differentially expressed circRNAs were found in elderly patients with OP, and through further experiments, it was found that circRNA008876 can play a biological role as an miR-150-5p sponge ( 49 ), which provides a potential biomarker and therapeutic target for senile OP. A previous study showed that Shh coreceptor growth arrest-specific 1 (GAS1) is expressed in mesenchymal cells, and in a GAS1-deficient mouse model, mice have abnormal dentition ( 50 ). Another study has also shown that inhibiting the expression of circ_0003865 in patients with OP can promote the osteogenic differentiation of BMSCs, and that circ_0003865 regulates the expression of the GAS1 gene by sponging miR-3653-3p ( 51 ).…”
Section: Associations Between Circrnas and Bmscsmentioning
confidence: 99%
“…Previous studies have indicated that elevated WNT signaling and decreased Hedgehog signaling leads to abnormal molar patterning and supernumerary tooth formation in mice ( 37 , 38 ). We therefore investigated WNT signaling changes in E16.5 Evc2 global mutant molars using LEF1 as a readout of active WNT signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Our data indicate that GAS1 can be secreted in the metanephros, therefore the requirements for GAS1 in a specific pathway (e.g., HH versus RET) could depend on whether it is acting in a cell-autonomous manner (i.e., membrane-tethered) or in a non-cell autonomous fashion (i.e., secreted). GAS1 may also act on multiple signaling pathways simultaneously in a single tissue during development, as suggested for gut development, forebrain development and dentition patterning (Biau et al, 2013; Marczenke et al, 2021; Seppala et al, 2022).…”
Section: Discussionmentioning
confidence: 99%